Analisa Integrasi Lean Manufacturing dan Metode Penugasan (Assignment Method) untuk Peningkatan Optimasi Operasi Workover (Studi Kasus: Sumur MN-0153, Lapangan Minagish, West Kuwait) - Cahyo Ady Pratomo; Syamsuri Syamsuri (Institut Teknologi Adhi Tama Surabaya, 2026)
Optimizing workover operations in the oil and gas industry poses significant challenges in balancing resource efficiency and execution time. Previous studies explored lean manufacturing as a strategy to cut waste and the assignment method as a tool to optimize resource allocation. However, few have combined both approaches within the context of workover operations. This study addresses that gap by analyzing how lean manufacturing and the assignment method can work together to improve efficiency in the workover of Well MN-0153 at the Minagish Field, West Kuwait.The research uses a quantitative approach, focusing on operational data analysis and resource optimization. Data came from field observations, document reviews, and interviews with operational personnel. The integration model was built through Lean-based waste analysis and optimized resource allocation using the Assignment Method. Results indicate that combining the two methods shortens work duration and improves both equipment and workforce utilization.This study contributes an optimization model that enhances productivity and reduces operational expenses in workover projects. It also offers practical recommendations for the oil and gas industry to streamline work processes through a more systematic and efficient approach. Keywords: Lean Manufacturing, Assignment Method, workover, efficiency, optimization, oil and gas